2004
DOI: 10.1063/1.1704618
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and x-ray magnetic circular dichroism in uranium monochalcogenides

Abstract: The electronic structure and x-ray magnetic circular dichroism (XMCD) spectra of US, USe, and UTe are investigated theoretically from first principles, using the fully relativistic Dirac LMTO band structure method. The electronic structure is obtained with the local spin-density approximation (LSDA), as well as with a generalization of the LSDA+U method which takes into account that in the presence of spin-orbit coupling the occupation matrix of localized electrons becomes non-diagonal in spin indexes. The ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 83 publications
(103 reference statements)
7
27
0
Order By: Relevance
“…These authors also used a wide range of U values varying between 0 and 4.5 eV, to find the proper U value, but in the LSDA þ U approach. Also several authors of earlier papers on various uranium compounds [44,50,51] As expected, both papers by Settai et al [52] as well as Biasini and Tro c [27] reported that, under the assumption that the 5f electrons are itinerant (as in this work), the non-magnetic FS of UGe 2 , obtained by the LAPW method within LDA, exists in three bands and is in overall agreement with our results.…”
Section: Band Structure and Fermi Surfacesupporting
confidence: 92%
“…These authors also used a wide range of U values varying between 0 and 4.5 eV, to find the proper U value, but in the LSDA þ U approach. Also several authors of earlier papers on various uranium compounds [44,50,51] As expected, both papers by Settai et al [52] as well as Biasini and Tro c [27] reported that, under the assumption that the 5f electrons are itinerant (as in this work), the non-magnetic FS of UGe 2 , obtained by the LAPW method within LDA, exists in three bands and is in overall agreement with our results.…”
Section: Band Structure and Fermi Surfacesupporting
confidence: 92%
“…We used the PY-LMTO-LSDA code (relativistic version 5.00.4) developed by Perlov and Yaresko according to principles detailed elsewhere [73][74][75][76]. Following MacDonald and Vosko [77], the Dirac HamitonianĤ D can be decomposed aŝ H D ¼Ĥ 0 þĤ m witĥ Gunnarson and Lundqvist [79]; Morruzzi-Williams-Janak [80]; Vilk-Nusair-Vosko [81]; Perdew and Zunger [82]; Perdew and Wang [83].…”
Section: Relativistic Lmto-lsda Calculationsmentioning
confidence: 99%
“…In principle, the screened Hubbard's repulsion parameter U, which enters the expressions for the matrix elements of V ee , could be estimated from constrained LSDA calculations. In practice, however, U is most often treated as an adjustable parameter, as well as the Stoner exchange parameter J [75].…”
Section: Relativistic Lmto-lsda Calculationsmentioning
confidence: 99%
“…The details of the computational method are described in our previous papers [40,41], and here we only mention some aspects specific to the present calculations. The calculations (corresponding to zero temperature) were performed for the experimentally observed lattice constant a = 5.416 Å using the fully relativistic linear-muffin-tinorbital (RLMTO) method [42,43].…”
Section: Crystal Structure and Computational Detailsmentioning
confidence: 99%